2020
DOI: 10.1029/2020jc016370
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric Influences on Antarctic Ice‐Shelf Melt Rates

Abstract: The bathymetry of the ocean exerts a leading order influence on ocean circulation, both at global and regional scales (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Ultimately model validation will remain a challenge until more direct observations of sub-ice shelf ocean conditions are made in tandem with measurements of melt rate. Adjoint models are powerful tools to assess model uncertainties and incorporate observations into numerical ocean models (Errico, 1997;Heimbach and Losch, 2012;Goldberg et al, 2020;Nakayama et al, 2021b). We showed preliminary adjoint sensitivity results for an idealised grounding zone domain, which clearly showed a 'reverse' ice-pump mechanism.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Ultimately model validation will remain a challenge until more direct observations of sub-ice shelf ocean conditions are made in tandem with measurements of melt rate. Adjoint models are powerful tools to assess model uncertainties and incorporate observations into numerical ocean models (Errico, 1997;Heimbach and Losch, 2012;Goldberg et al, 2020;Nakayama et al, 2021b). We showed preliminary adjoint sensitivity results for an idealised grounding zone domain, which clearly showed a 'reverse' ice-pump mechanism.…”
Section: Discussionmentioning
confidence: 80%
“…The first used the MITgcm ocean model to simulate the Pine Island Ice Shelf cavity (Heimbach and Losch, 2012). Goldberg et al (2020) extended MITgcm's adjoint model, such that it was able to calculate the sensitivity of melt rate to bathymetry. Notably, this was using the open source AD tool, openAD (Utke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Finite volume techniques are employed yielding an intuitive discretization and support for the treatment of irregular geometries using orthogonal curvilinear grids and shaved cells in this model (Marshall et al, 1997). On the other hand, there are several uncertainties in MITgcm, such as atmospheric boundary conditions (Aran et al, 2016), geology and ice (Goldberg et al, 2020). In this study, these uncertainties are less important because the deep SCS circulation is not closely related to the atmosphere and sea ice.…”
Section: Modelmentioning
confidence: 99%
“…Previous studies have shown that the bathymetry of the Antarctica continental slope directly controls the water mass exchanges between the deep ocean and the shelf seas (Walker et al, 2007;Thoma et al, 2008;Nicholls et al, 2009;Hellmer et al, 2012;Pritchard et al, 2012), especially for the intrusion of modified Circumpolar Deep Water (mCDW) onto the continental shelf (Nitsche et al, 2007;Millan et al, 2017;Nitsche et al, 2017;Tinto et al, 2019). Therefore, the accurate high-resolution ocean bathymetry data is favorable in precisely delineating the pathways of mCDW onshore intrusion and consequent influences on the ice shelf melting rates (Nakayama et al, 2019;Goldberg et al, 2020;Eisermann et al, 2021). The bottom topography can also regulate the tidal dynamics and hence their impacts on the ice shelf melting and stability (Padman et al, 2002;Griffiths and Peltier, 2009;Makinson et al, 2011;Rosier et al, 2014;Padman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the detailed representation of the bathymetry is critical to properly simulate the cross-shelf transport of warm water into the sub-ice-shelf cavities (Millan et al, 2017;Nitsche et al, 2017;Millan et al, 2020). Numerical studies have also focused on the influences of the high-resolution sub-ice-shelf geometry on the circulations under the ice shelf and the ice shelf basal melting (Goldberg et al, 2020;Millan et al, 2020). Despite that some corrected high-resolution bathymetry data sets of the Antarctic continental shelf have been compiled (Dickens et al, 2014;Nitsche et al, 2017;Smith et al, 2021;Tao et al, 2021), the influences of the bathymetry corrections on the circulations, water mass properties, and the basal melting of ice shelves have not been clarified.…”
Section: Introductionmentioning
confidence: 99%